Machine learning approach to identify adverse events in scientific biomedical literature - Sonja Wewering; Claudia Pietsch; Marc Sumner; Kornél Markó; Anna‐Theresa Lülf‐Averhoff; David Baehrens (Wiley, 2022)
Abstract Monitoring the occurrence of adverse events in the scientific literature is a mandatory process in drug marketing surveillance. This is a very time‐consuming and complex task to fulfill the compliance and, most importantly, to ensure patient safety. Therefore, a machine learning (ML) algorithm has been trained to support this manual intellectual review process, by automatically providing a classification of the literature articles into two types. An algorithm has been designed to automatically classify "relevant articles" which are reporting any kind of drug safety relevant information, and those which are not reporting an adverse drug reaction as "not relevant." The review process is consisted of many rules and aspects which needed to be taken into consideration. Therefore, for the training of the algorithm, thousands of documents from previous screenings have been used. After several iterations of adjustments and fine tuning, the ML approach is definitively a great achievement in pre‐sorting the articles into "relevant" and "non‐relevant" and supporting the intellectual review process.